Modulation of spin-orbit torque efficiency by thickness control of heavy metal layers in Co/Pt multilayers - Sethi, Pankaj (2017)
We investigate and quantify spin-orbit torque (SOT) strength by current induced effective in-plane magnetic fields and spin Hall angle (SHA) using AC harmonic Hall voltage measurements techniques on Ta/Pt/Co/Pt/Co/Ta thin film structures. The proposed Co/Pt thin film double stack gives property enhancement on thermal stability and perpendicular magnetization anisotropy strength over the single stack Pt/Co/Ta. In the proposed Co/Pt double stack we observed that increasing the Ta capping thickness to three times enhances the SHA in similar order, consistent with larger spin injection efficiency. Doubling the Pt spacer layer thickness reduces the SHA by nearly 1.4 times, due to partial cancellation of SOT by bottom layer Pt, negating the increase from the top Co/Pt interface. The in-plane current threshold for magnetization switching is lower with the increase of the SHA.